OBSERVATION OF EARTH TIDES AND EARTH'S FREE OSCILLATIONS WITH A SUPERCONDUCTING GRAVIMETER AT SYOWA STATION (STATUS REPORT) - サトウ, タダヒロ; シブヤ, カズオ; オカノ, ケンタ; カミヌマ, カツタダ; オオエ, マサツグ; SATO, Tadahiro; SHIBUYA, Kazuo; OKANO, Kenta; KAMINUMA, Katsutada; OOE, Masatsugu (National Institute of Polar Research, 1993)
P(論文) Superconducting gravimeter (SCG) observation is believed to offer high sensitivity and high resolution data for study of the Earth's core dynamics. We describe the importance of SCG installation at Syowa Station at high southern latitudes (69.0°S) for weak signal detection of fluid core resonance, core undertones, Slichter mode, etc. In order to assess the SCG capability as a long-period seismometer, parallel observations using a Streckeisen seismometer and a LaCoste & Romberg type-D gravimeter with the same data acquisition systems are planned. Although leakage of liquid helium from the SCG dewar during the installation procedure in the 33rd Japanese Antarctic Research Expedition (JARE-33 : February 1992) delayed the start of the SCG observation, a retrial was performed during JARE-34 (February 1993). The installation proved successful, although fine tuning may still be required. departmental bulletin paper